Учимся работать на компьютере - Антошин Максим Константинович (Внимание: дети!, 2007)
Экземпляры: ДБ; ф7; ф13 (20221222) / Инвентарный номер: 44627 / Цена: 55.40 / Сис.шифр: 32.973мл / Авт.знак: А 72 / ГРНТИ: 20 / ББК: 32.973мл